Transformasi Pemahaman Mazhab dalam Pendidikan Islam dari Fanatisme menuju Toleransi - Dwi Aghniya Ilmi; Muhammad Assyf Arron Zanzabil; Qonita Khoerunnisa; Mohammad Ikhsan Maulana Al-Adli; Siyono Siyono (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
Madhhab fanaticism in Islamic education, which appears in fiqh teaching practices that tend to absolutize a single madhhab, restrict dialogical space, and insufficiently appreciate the diversity of scholarly opinions. Such conditions may foster exclusive and intolerant religious attitudes among students. To respond to this problem, the study employs a qualitative approach with a library research design by critically examining books, journal articles, and documents related to fiqh madhhabs, Islamic education, religious moderation, and multicultural education. The data are analyzed using content analysis and descriptive–analytical techniques to map the forms of madhhab fanaticism in the learning process, the stages of transformation in madhhab understanding, and the pedagogical strategies that support the emergence of tolerant attitudes. The findings indicate that the transformation toward a more tolerant understanding of madhhabs is supported by curricula that accommodate comparative fiqh (multi-madhhab), inclusive learning materials, dialogical teaching methods, and teachers’ role modeling of moderate attitudes. Inhibiting factors include deeply rooted madhhab fanaticism, the dominance of conservative curricula, ideological bias in textbooks, and a weak culture of critical thinking. It is concluded that strengthening fiqh instructional design that consciously integrates religious moderation and multicultural education is essential for shifting madhhab understanding from patterns of fanaticism to patterns of tolerance within Islamic educational institutions.